ISLAMIC EDUCATION LEARNING MODEL IN NATURAL ELEMENTARY SCHOOL OF AR-RIDHO - Faisol, Muhammad Aris; Raharjo, Raharjo (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This study aimed to know the learning plan, implementation, and evaluation of Islamic Education lessons. The method used in this research was qualitative research with a phenomenological approach. Data were collected through interviews, observation, and documentation. The subjects of this study were principals, teachers, and students of Ar-Ridho Elementary School. The results indicated that the lesson plan consisted of determining the theme for one semester, making theme analysis, spider-web, weekly planning sheets, and writing daily activities. The Natural elementary school of Ar-Ridho used an integrated thematic model with spider-web or linked one theme with several lessons, which emphasizes aqidah (believes), 'akhlaq (moral), and fiqh (knowledge). Evaluation of learning used written, oral, and practical assignments that referred to cognitive, affective, and psychomotor aspects. Therefore, Islamic education already has a good learning plan, implementation, and evaluation, but several things still need improvement for better learning. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana rencana, penerapan, dan evaluasi pembelajaran dari pelajaran Pendidikan Agama Islam (PAI). Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan pendekatan fenomenologi. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Subjek penelitian ini adalah kepala sekolah, guru, dan siswa SD Alam Ar-Ridho. Hasil penelitian menunjukkan bahwa rencana pembelajaran terdiri dari penentuan tema untuk satu semester, membuat analisis tema, spider web, weekly planning sheet atau lembar rencana mingguan, dan menulis kegiatan sehari-hari. SD Alam Ar-Ridho menggunakan model tematik terpadu dengan spider web atau mengaitkan satu tema dengan beberapa pelajaran, yang menekankan pada akidah, akhlak, dan fiqih. Evaluasi pembelajaran menggunakan teknik tes tertulis, lisan, dan tugas praktek yang mengacu pada aspek kognitif, afektif, dan psikomotorik. Dapat disimpulkan bahwa pembelajaran PAI sudah memiliki rencana, pelaksanaan, dan evaluasi pembelajaran yang baik, tetapi beberapa hal masih perlu ditingkatkan dan diperbaiki untuk pembelajaran yang lebih baik.